Prolonged intermittent kidney replacement therapy: overcoming challenges in the critically ill patient in low-resource settings - Abdelhamid, Yasser M (African Journal of Nephrology, 2026)
Acute kidney injury is a frequent complication of critical illness in intensive care units and has a negative prognostic impact. Kidney replacement therapy (KRT) is frequently needed and the treatment modalities used in these settings include continuous kidney replacement therapy (CKRT), intermittent haemodialysis (IHD) and peritoneal dialysis (PD). Haemodynamic instability is common in critically ill patients and the different KRT modalities affect haemodynamics in different ways. CKRT is often considered the modality of choice due to its lower dialysate flow, extracorporeal blood flow and ultrafiltration rates, leading to better haemodynamic stability. In poor socio-economic settings, however, the high cost of CKRT is a major barrier limiting its widespread use. This brief narrative review makes the case for increased use of prolonged intermittent kidney replacement therapy (PIKRT), frequently called sustained low-efficiency dialysis (SLED), a form of KRT that uses standard IHD machines to deliver prolonged dialysis sessions at reduced flow rates, with good haemodynamic stability, and at a lower cost. PIKRT is an effective alternative for treating acute kidney injury in critically ill patients in low-resource settings.